Biomolecular engineering of a human beta defensin model for increased salt resistance - Li, Xiang (2013)
Human beta defensins (hBDs) are natural antimicrobial peptides (AMPs) with broad spectrum antimicrobial activity. However, hBDs, like many AMPs, are easily inactivated by salt, which limits their extracellular applications as antimicrobial coating agents. In this study, a salt-resistant hBD28 peptide was designed by increasing C-terminus cationicity of the wild type peptide via rational amino acid substitution. The mutant hBD28 exhibited salt-tolerance behaviour and improved antimicrobial potency compared to wild type hBD28. Zeta potential analysis confirmed that increased cationicity was crucial to overcome salt-induced charge-shielding effects, which enhanced peptide–membrane interaction compared to the wild type peptide. The mutant hBD28 did not exhibit obvious differences with respect to hydrophobicity, oligomerization ability, and secondary structure compared to the wild type peptide. A simple design strategy to overcome salt-inactivation in hBD28 is demonstrated through this study, which will guide the design of other salt-resistant AMPs to accelerate their development as anti-infective agents in ionic environments.